Nicotinamide inhibits corneal endothelial mesenchymal transition and accelerates wound healing. (July 2019) - Li, Zongyi; Duan, Haoyun; Li, Wenjing; Jia, Yanni; Zhang, Songmei; Zhao, Can; Zhou, Qingjun; Shi, Weiyun
Abstract: Corneal endothelial cells (CECs) maintain the clarity of the cornea through the barrier and pump function. Ex vivo culture or injury may cause corneal endothelial-mesenchymal transition (EnMT) and lead to loss of function. In this study, we explored the effects of nicotinamide (NIC) on the wound healing of rabbit corneal endothelium and the proliferation, migration, and EnMT of cultured human CEC lines. The animal results showed that corneal clarity was rapidly recovered within seven days through topical application of NIC in the rabbits with mechanical injury of the corneal endothelium, while the control corneas remained edematous and cloudy. Whole-mounted corneal staining found the expressions of Na + /K + -ATPase, aquaporin-1, and zonula occludens-1 were mainly localized to the boundaries of regenerated endothelium in NIC-treated eyes, in contrast to the scattered staining in vehicle-treated eyes. Interestingly, we found that NIC application inhibited the expression of typical EnMT marker alpha-smooth muscle actin, which appeared in the rabbit corneal endothelial wound healing. In vitro, NIC promoted the proliferation, but not the migration, of cultured human CECs. Moreover, NIC effectively inhibited transforming growth factor beta-1-induced corneal EnMT and decreased the levels of EnMT regulators snail and slug. Therefore, our study indicates that NIC enhances corneal endothelial wound healing through the promotion of proliferation and the inhibition of EnMT, which may provide a potential pharmaceutical agent for treating corneal endothelial dysfunction. Highlights: The topical NIC application enhanced wound healing of corneal endothelium in a rabbit model. NIC significantly promoted the proliferation of cultured human CECs. NIC inhibited TGFβ1-induced corneal EnMT in the cultured human CECs.